THE PROTECTION OF INTRACELLULAR BRUCELLA AGAINST THERAPEUTIC AGENTS AND THE BACTERICIDAL ACTION OF SERUM - Shaffer, James M. (The Rockefeller University Press, 1953)
A method for the in vitro study of intracellular brucella has been described. Exudative leukocytes containing intracellular brucella have been maintained in vitro in a synthetic tissue culture medium or in human or animal serum. Intracellular brucella are protected in vitro against the lethal action of therapeutic agents or the bactericidal action of serum. This protection of intracellular brucella is dependent upon the presence of an intact, viable host cell. None of the currently available therapeutic agents, whether used alone or in combinations, were capable of killing all intracellular brucella in vitro in 24 hours. A remarkable protection of intracellular brucella against streptomycin has been demonstrated. The most effective reduction in the number of viable intracellular brucella was accomplished by exposure of the host cells to streptomycin plus aureomycin, terramycin, or chloramphenicol. The available evidence suggests that the ability of brucella to localize and remain viable within the cells of an infected host is an important biologic factor in establishing and perpetuating brucella infections, despite therapeutic measures or the operation of the host's humoral defense mechanisms. Reduction of neotetrazolium by leukocytes and brucella in vitro provides a method for assessing the metabolic status of the host cell, but does not discriminate with any degree of certainty a viable from a non-viable intracellular organism.